Modern treatment methods in heart failure. What can we do to improve prognosis? - Czarnecka, Danuta; Kusak, Piotr (Przewodnik Lekarza/Guide for GPs, 2009)
Heart failure is a more and more significant medical problem. We can observe an increasing tendency in morbidity but simultaneously we are reducing mortality in this disease. Many therapeutic possibilities which are the basis of heart failure treatment have been well known for many years and are well proven in many clinical trials. Nowadays we are trying to optimize the methods we know, both pharmacological and instrumental. Lately, we have also been focusing on non-pharmacological interventions due to their lower cost and high efficacy as well. Dynamic development of modern instrumental methods and crossing borders in medicine leads to more possibilities for the patient and doctor to choose to treat both diseases implicated in the aetiology of heart failure and heart failure as well. Finally, new methods are being instituted which not only expand our possibilities but also improve the prognosis. A new proposal is polyunsaturated fatty acids omega-3. Their efficacy has strong proof in the GISSI-HF randomized trial. Unfortunately clinical efficacy of the new therapeutic methods is more difficult to prove. For example, clinical effectiveness of statins has not been proved by two large trials (CORONA and GISSI-HF). Therefore even a very small improvement of the prognosis in this group of patients is a great success for medicine.